2015
DOI: 10.1523/jneurosci.0950-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-  Impairs Synaptic Inhibition via GABAA Receptor Endocytosis

Abstract: Amyloid ␤ (A␤) is thought to play an important role in the pathogenesis of Alzheimer's disease. A␤ may exert its neurotoxic effects via multiple mechanisms and in particular through degradation of excitatory synaptic transmission associated with impaired synaptic plasticity. In contrast, much less is known about A␤ effects at inhibitory synapses. This study investigates the impact of acute A␤1-42 application on GABAergic synaptic transmission in rat somatosensory cortex in vitro. Whole-cell voltage-clamp recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 34 publications
3
79
0
1
Order By: Relevance
“…For example, the precise mechanism(s) through which Aβ disrupts NREM sleep physiology, specifically within slow oscillation frequency range (<1Hz), is unknown. One tenable candidate that we offer is Aβ-disruption of frontal NMDA and GABA A receptor function that underlies NREM slow oscillation expression in cortical regions known to accumulate Aβ early 4345 . The low frequency (<1Hz) slow oscillations of NREM sleep are governed by NMDA and GABA A receptor activity, the former dictating a cellular UP state of cortical excitation, the latter the DOWN state involving prolonged hyperpolarization 44 .…”
Section: Sleep Aβ and Alzheimer’s Diseasementioning
confidence: 99%
“…For example, the precise mechanism(s) through which Aβ disrupts NREM sleep physiology, specifically within slow oscillation frequency range (<1Hz), is unknown. One tenable candidate that we offer is Aβ-disruption of frontal NMDA and GABA A receptor function that underlies NREM slow oscillation expression in cortical regions known to accumulate Aβ early 4345 . The low frequency (<1Hz) slow oscillations of NREM sleep are governed by NMDA and GABA A receptor activity, the former dictating a cellular UP state of cortical excitation, the latter the DOWN state involving prolonged hyperpolarization 44 .…”
Section: Sleep Aβ and Alzheimer’s Diseasementioning
confidence: 99%
“…These two studies have shown that the β2/3 subunits are relatively resistant to alteration in AD patients [126]. Ulrich [127] investigated the effect of Aβ peptides on synaptic transmission through the GABA (A) receptor-mediated endocytosis mechanism and found that Aβ may weaken synaptic inhibition through downregulation of GABA (A) receptors and reversed in the presence of GABA (A) receptor agonist (isoguvacine).…”
Section: Neurotransmitter-based Therapeutics In Admentioning
confidence: 99%
“…In a separate study of the fimbria-CA3 complex postsynaptic response, Aβ also induces a significant decrease in late inhibitory postsynaptic currents (IPSCs) (Nava-Mesa et al, 2013). Treatment of somatosensory neurons with soluble Aβ as much as 1 µM has also been found to decrease agonist-evoked GABA A responses and to depress monosynaptic GABA A receptor-mediated IPSCs to 60% of control levels on average, whereas a reversed sequence control peptide is ineffective (Ulrich, 2015). The downregulated GABA A receptors for Aβ-mediated synaptic inhibition are due to increased endocytosis of GABA A receptors, because the induced IPSC decline was prevented by intracellular applications of p4, a peptide inhibitor to block the dynamin-mediated removal of GABA A receptors from the plasma membrane.…”
Section: Aβ and Synaptic Functionsmentioning
confidence: 99%